Chapter De complete clitoris ontdekt, vergeten en genegeerd? - Hollewand, Karen (Amsterdam University Press, 2022)
Although in recent years more and more attention has been paid to the clitoris, often little attention to the attitude towards her existence in the past. This article takes a look at the clitter's history and focuses on her appear in Dutch publications by (and for) doctors and teachers in the last 400 years. The conclusion is that the clitoris has never been completely forgotten or ignored, but that the ignorance about this female organ is due is due to cultural and social factors: a lack of attention to sexuality in general and for the female genitalia in particular. pass in the last decade this has been slowly changing: attention to the full anatomy of the clitoris is widely used for the first time combined with attention to the sexual experience of women within a framework in which she is equal to the man.